THE CONCEPT OF TAUHID EDUCATION IN THE FAMILY ENVIRONMENT: STUDY OF HAMKA'S PERSPECTIVE - Muhammad Dwi Fajri; Didin Saepudin; Bahrudin; Ibdalsyah (Profetika: Jurnal Studi Islam, 2023)
This study aims to examine and describe Buya Hamka's concept of aqidah education in the family environment. This research uses qualitative research with literature study with Intellectual biography approach. The techniques are content analysis methods and interpretation methods. The results of the study show that Hamka in thoughts about Tawhid emphasizes that monotheism will make a believer form a strong and steadfast soul, freedom of the soul, personal independence, and loss of fear in facing the difficulties of life, courage to face all difficulties, so that there is no difference between life and death, as long as to seek the pleasure of Allah SWT. For Hamka that Tawhid in fostering a family is the foundation of a Muslim family. Thus the concept of Hamka in building monotheism in the family environment is carried out, namely first, planting monotheism. Second, monitoring beautiful children. Third, love and care for each other.